Pocket book of technical writing for engineers and scientists. - Finkelstein, Leo, Jr. (Boston McGraw-Hill, 2008)
The focus of this text is to teach engineering students the skill of technical writing. The book is unique in that it gets to the point, uses practical outlines throughout, and shows students how to produce the most common technical documents step-by-step, in a manner that is fun and interesting to students. Each chapter has an end-of-chapter critique which allows students to implement what they have learned in the chapter. With ABET increasing the emphasis on technical writing, this affordable, straightforward, easy-to-understand text with flexible coverage, would be a perfect fit for your technical writing course.